Human Capital Disain Interior ISI Yogyakarta Dalam Persaingan Di Era Digital - M. SholahuddIn (Ars: Jurnal Seni Rupa dan Desain, 2010)
Interior Design Study Program’s Human Capital in the Competition of  Digital Era. The growth of  information  technology that then followed by the globalization forces  the higher education institutions to revitalize their selves and to reconsider their business and working concept.  The most urgent thing to be done in identifying the nation competences and then translating and ultimately  selling those competences in global market is producing exceptional human capital. Higher education institution is responsible to run that function. Human capital development program undertaken by  the Interior Design Study Program of  ISI Yogyakarta is based on the market need of  professional interior  designers. Some efforts have been carried out in the program i.e. formulating the vision and mission to be  accomplished, identifying the existing problems, and setting a curriculum that fits the market need.Keywords: human capital, interior design, interior designer, interior  decorator, curriculum